APPLICATION OF UTILIZATION OF RENEWABLE ENERGY SOURCES WITH METHODS SOLAR CELL IN SUKADAYA CIKULUR LEBAK BANTEN VILLAGE - Panulisan, Bambang Setyo; Khaerudin, Dedi; Riyandani, Alvi; Suhaerudin, Erik; Virgiawan, Muhammad Vikry (Nindikayla Institute, 2024)
In the era of industrial technology 4.0 we are required to know and use emerging technologies. One of the technologies that need to be known is regarding solar cells as a renewable energy source. The implementation of solar cell utilization also needs to be done as concrete evidence of reducing electricity consumption derived from fossil energy sources that cause much pollution. The purpose of this community service is to improve insights and facilities through the utilization of renewable energy. Increased insight is done by socializing partners about the workings and advantages of solar cells. While the improvement of facilities is done by presenting portable solar cells and solar-powered lights. Based on the survey conducted, the implementation of this activity received an excellent response and partners expect other programs.